Evaluating the Properties of a Dual-Effect Facial Injectable: From Preclinical Data to Real-World Evidence - Ormiga P; Hernández CA; de Lima Romeiro R; Bernardin A; Sambatti Crema F; Nakab L; Shklanovsky L; Kerson G (Clinical, Cosmetic and Investigational Dermatology)
Patricia Ormiga,1 Claudia A Hernández,2 Rogério de Lima Romeiro,3 Aude Bernardin,4 Fabio Sambatti Crema,5 Lauren Nakab,6 Lital Shklanovsky,7 Graeme Kerson8 1Clínica Patricia Ormiga, Rio de Janeiro, Brazil; 2CH Dermatologia, Medellin, Antioquia, Colombia; 3Faculdade São Leopoldo Mandic, Instituto São Leopoldo Mandic, Área de Harmonização Orofacial, São Paulo, Brazil; 4Allergan Aesthetics, an AbbVie company, Pringy, France; 5Allergan Aesthetics, an AbbVie company, São Paulo, Brazil; 6Allergan Aesthetics, an AbbVie company, Irvine, CA, USA; 7Allergan Aesthetics, an AbbVie company, Lod, Israel; 8Allergan Aesthetics, an AbbVie company, Marlow, UKCorrespondence: Patricia Ormiga, Clínica Patricia Ormiga, Av. Ataulfo de Paiva, 204 – Sala 908, Leblon, Rio de Janeiro, Brazil, Tel +21 98805-1848, Email paormiga@gmail.com